Vita Hugonis Marchianensis († 1158) Présentation, édition critique et traduction française - Platelle, Henri (Analecta Bollandiana, 1993)
Critical edition and French translation of the Life of Hugo, abbot of Marchiennes (BHL 4031d) previously available only in a bad edition by Martène. The Life was compiled by an eyewitness who paid particular attention to the psychology of his hero. Although sometimes accorded the title of "Blessed", Hugo of Marchiennes has never been the object of a public cult.